Recognizing the University's Role in Mental Health Promotion - Eltayeb, Shahla (Journal of Educational and Psychological Sciences, 2022)
Introduction: Mental health is a state of wellbeing that enables individuals to cope and function with daily stressors; hence promoting mental health is an integral part of global public health that aims to maximize individual and societies to attain sustainable development goals. Aim of study: The current study aims to determine the level of universities' actual roles in promoting mental health and the modalities that universities undertake to promote mental health in Saudi Arabia. Materials and methods: This cross-sectional study conducted among eleven Saudi governmental universities, the sample stratified into three categories: employees, faculty members, and students. The study developed and validated a 30 items scale the University Mental Health Promotion Scale is the first scale of its kind in the Arab world designed to measure the level of universities' actual roles in promoting mental health. Results: The University Mental Health Promotion Scale’s showed good validity and reliability with an internal consistency ranged between 0.543 and 0.761 and alpha Cronbach of 0.88. The findings indicate the level of universities' roles in promoting mental health is medium with a mean score (53.05) of (90) degrees. The five mental health promotion subscales showed that creating a supportive environment ranked as the highest (56%) factor promoted by universities, followed by developing personal skills with a relative weight of (51%). Conclusion: Universities are currently promoting mental health through mainly environmental changes; nevertheless, mental health policies, capacity building, and community coordination are yet to be attained. The findings from our study offer important insight to university educators and administrators about the role they can play in better supporting student wellbeing and preventing high rates of psychological distress. We argue that the process of promoting mental health will create a conducive environment and act on students’ sense of inclusion and empowerment, and this is critical given that the goal of improving student mental well-being can only be achieved through effectively promoting mental health in universities.
Keywords: Mental health promotion; University Education; Ottawa Charter; Scale